2023
DOI: 10.3390/antibiotics12081343
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Pharmacists’ Viewpoint on Quality Use of Antibiotics and Resistance: A Qualitative Exploration from a Tertiary Care Hospital of Quetta City, Pakistan

Maryam Farooqui,
Zaffar Iqbal,
Abdul Sadiq
et al.

Abstract: Suboptimal antibiotics use and the development of antibiotic resistance is a universal calamity. The theoretical model of therapeutic efficacy correlates quality use of antibiotics with healthcare practitioners’ understanding of antibiotic use and resistance. Keeping this phenomenon in mind, we aimed to evaluate hospital pharmacists’ understanding of antibiotic use and resistance at a public healthcare institute in Quetta city, Pakistan. This was a qualitative study that employed a semi-structured interview gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 52 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…A patient’s decision to self-treat is informed by the perception that antimicrobials work based on prior therapeutic success with antimicrobials in themselves, family, or friends. Antimicrobials for self-treatment are obtained by receiving medication from a friend or family member, using leftover medication, or directly obtaining medication without a prescription from a pharmacy [ 65 , 74 , 75 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A patient’s decision to self-treat is informed by the perception that antimicrobials work based on prior therapeutic success with antimicrobials in themselves, family, or friends. Antimicrobials for self-treatment are obtained by receiving medication from a friend or family member, using leftover medication, or directly obtaining medication without a prescription from a pharmacy [ 65 , 74 , 75 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies described a multitude of systemic barriers to accessing the formal health care system, including rural areas with limited infrastructure, long wait times, poor quality of care, an inability to pay for services, or the complexity of navigating health systems [ 73 , 74 , 87 ]. Instead of accessing formal care, many patients reported that they instead relied on informal drug vendors who ran small drug stores that provided consultations and dispensed medications [ 65 , 72 , 74 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients will "doctor shop" or seek care only from providers who are known to readily provide antimicrobials or pharmacies that are liberal with their distribution (65,(90)(91)(92).…”
Section: Individual Level: Patients and Their Caregiversmentioning
confidence: 99%